Increased Mortality with Co-existence of Crimean Congo Hemorrhagic Fever and COVID-19 - Elik, Dilşah Başkol; Oruç, Nevin; Güler, Ezgi; Erdem, Hüseyin Aytaç; Karbek Akarca, Funda; Sipahi, Oğuz Reşat; Özütemiz, Ahmet Ömer; Pullukçu, Hüsnü; Taşbakan, Meltem; Çiçek, Candan; Yamazhan, Tansu (Mediterranean journal of infection, microbes & antimicrobials, 2022)
SummaryCrimean-Congo hemorrhagic fever (CCHF) is an acute viral disease with fever and bleeding caused by a tick-borne virus belonging to the Bunyaviridae family. Coronavirus disease-2019 (COVID-19) is a novel disease caused by Severe Acute Respiratory Syndrome Coronavirus Type 2, which can lead to acute respiratory distress syndrome (ARDS). Here, we present a case with CCHF and COVID-19 co-infection to draw attention to the increased mortality in co-infection cases. A 77-year-old female patient with known hypertension was admitted to the emergency department with complaints of fever, nausea, vomiting, diarrhea, and myalgia for two days. There was no history of tick bite or contact with a patient with COVID-19. Current anamnesis and clinical and laboratory findings pre-diagnose the patient with CCHF, hemolytic uremic syndrome, and thrombotic thrombocytopenic purpura, leading to a ward admission. Crimean-Congo hemorrhagic fever was diagnosed after receiving a positive CCHF immunoglobulin M (indirect fluorescent antibody) result. A nasopharyngeal swab sample for COVID-19 real-time polymerase time reaction was sent due to a continuous fever and the development of shortness of breath on day three of hospitalization, which revealed positive results; thus, the patient was started on favipiravir treatment. The patient was transferred to the intensive care unit on day four due to increased oxygen demand and ARDS diagnosis. The patient died due to respiratory failure on the seventh day of hospitalization. COVID-19-related ARDS that overlapped on top of CCHF caused her to develop a cytokine storm and died despite her clinical parameter improvement due to CCHF. Crimean-Congo hemorrhagic fever and COVID-19 symptoms or findings can be confused because of their similarities, but the possibility of being seen together should not be overlooked. Concurrently, some similarities in the pathogenesis of these two diseases suggest that co-infection may worsen the clinical course; hence, new studies are needed on this subject.